(untitled) (Journal of Computational Mathematics, 2006)
This special issue of the Journal of Computational Mathematics is dedicated to Professor Qun Lin, an outstanding mathematician and a Member of Chinese Academy of Sciences (CAS), on the occasion of his seventieth birthday.